Function of ets genes is conserved between vertebrates and Drosophila. - Albagli, O.; Klaes, A.; Ferreira, E.; Leprince, D.; Klambt, C. (Mechanisms of Development, 1996)
The Drosophila pointed gene encodes two ETS transcriptional activators, pointedP1 and pointedP2, sharing a common C-terminal ETS domain. In the embryonic central nervous system pointedP2 is required for midline glial cell differentiation, whereas, in the eye, pointedP2 is essential for photoreceptor cell differentiation. Both vertebrate c-ets-1 and c-ets-2 gene ETS domains are highly homologous to the one of pointed. In addition, the N-terminal region of pointedP2 and vertebrate ets products share another homologous domain, the so-called RII/pointed box which appears to mediate the ras-dependent phosphorylation/stimulation. Here, we show that the vertebrate ets genes are functionally homologous to the Drosophila pointed gene. pointedP2 efficiently binds to an optimized c-Ets-1/c-Ets-2 probe in vitro, and stimulates two distinct c-Ets-1/c-Ets-2-responsive sequences when transiently expressed in vertebrate cells. Conversely, when vertebrate ets transgenes are expressed during fly development, they are capable of rescuing the pointed mutant phenotype in both midline glia and photoreceptor development. As ectopically expressed pointedP1 can also rescue pointedP2 deficiency in photoreceptor development, it appears that the ability of ets products to phenocopy each other in vivo does not require the conserved RII/pointed box, but rather, primarily relies on the presence of the highly conserved ETS domain.